Potassium Diformate : A New Alternative To Antibiotic Growth Promoters - Chowdhury, R; Haque, MN; Islam, KMS; Khan, MJ (Bangladesh Journal of Animal Science, 2012)
Potassium diformate (Formi) is odorless, low-corrosive and easy to handle. The European Union (EU) has approved it as non-antibiotic growth promoter, for use in non ruminant feeds. Maximum inclusion level of potassium diformate is 1.8% as registered by the European authorities which can improve weight gain up to 14%. Potassium diformate contains the active ingredients free formic acid as well as formate has the strong anti microbial effect in stomach and also in duodenum. Potassium diformate with its growth promoting and health enhancing effect has proven to be an alternative to antibiotic growth promoters. Its special effect on the micro flora is regarded as the main mode of action. 1.8% potassium diformate in growing pig diets also significantly increase Feed intake and feed conversion ratio was significantly improved where growing pig diets was supplemented with 1.8% potassium diformate. It was also reduced pH in the stomach and duodenum. potassium diformate 0.9% significantly reduced the pH of duodenal digesta. DOI: http://dx.doi.org/10.3329/bjas.v37i2.9887 BJAS 2008; 37(2): 99-105